Instruments Used For The Measurement Of Quality Of Life Related To Health During The Climacteric - Ayala-Peralta, Félix (2016)
The evaluation of quality of life should focus mainly on the patient’s perception of her state of health, being an activeparticipant in this process. Instruments for measuring health-related quality of life (HRQL) can be classified into genericinstruments that measure multiple areas or domains and that are applicable to all individuals, regardless of the pathologythat affects them; And specific instruments, which are those that measure the functioning of the patient in one or severalareas and are characterized by paying particular attention to those symptoms or problems specific to a particular diseaseand those areas considered to be most affected, being only applicable to patients Specific. In daily clinical practice it is usefulto evaluate: improvement of clinical diagnosis, individualization and prioritization of treatments, improving the doctor-patientrelationship, and monitoring compliance with therapies that contribute to the improvement of the female quality of life.